Modalizatory jako wielowymiarowe zagadnienie w nauce języka szwedzkiego - Kowal, Iwona (Neofilolog, 2021)
Sentence adverbials build a multidimensional constituent in many languages, i.e. they can, among others, modify the meaning of the entire sentence, emphasize a particular element in it, or build the coherence in texts. Due to the multifaced character of this linguistic phenomenon the acquisition of it in foreign language learners can be a complex process. The learner is not only faced with a variety of different words and phrases that can be used in order to deliver a complementary information in the text, but also, depending on the structural requirements of the specific language, has to learn to put this constituent in the correct place in the sentence. In present paper the use of sentence adverbials in Polish learners od Swedish will be presented. The data considered in the analysis comprises two types of texts: a summary of an expository text and a narrative. The results show that foreign language learners at the intermediate stage of the language use a broad repertoire of sentence adverbials and place them in appropriate contexts. In narratives modal expressions predominate, while in summaries connectives and intensifiers are used more often. The learners can place sentence adverbials correctly in the sentence, especially in main clauses. However, the word order in dependent clauses when other sentence adverbials occur, except for sentences with the negation inte, is still under development.